Nicholas Cook, The Schenker Project. Culture, Race, and Music Theory in Fin-de-siècle Vienna (2007) - Cascelli, Antonio (Journal of the Society for Musicology in Ireland, 2009)
A review of Nicholas Cook, The Schenker Project. Culture, Race, and Music Theory in Fin-de-siècle Vienna (New York: Oxford University Press, 2007) ISBN 978-0-1951-7056-6